2017
DOI: 10.1177/1934578x1701201117
|View full text |Cite
|
Sign up to set email alerts
|

Proliferation Effects on Hair Growth of Compounds Isolated from the Bark of Dalbergia oliveri

Abstract: One new isoflavane, 7,4′-dihydroxy-isoflavanquinone (1), together with ten known compounds (2-11) were isolated from the bark of Dalbergia oliveri Prain. The structures of compounds were determined on the basis of extensive spectroscopic methods, including 1D and 2D NMR and CD spectroscopic data. Using a cell proliferation assay, the isolated compounds were evaluated for their proliferation effects on hair growth. (3R)-5'-Methoxyvestitol (2) and (6aR,11aR)-3,8dihydroxy-9-methoxypterocarpan (10) significantly i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…The presence of an olefinic group [δ H 8.27-8.33 (H-2)/δ C 152.7-153.1 (C-2), and δ C 123.1-124.7 (C-3)] and a ketone carbon δ C 174.5-174.6 (C-4) in the 1 H-and 13 C-NMR spectra indicated 1, 2, and 5 to be isoflavones. 16,20 Comprehensive analysis of the 1 H-and 13 C-NMR spectra of 1 showed that 1 possessed 7 aromatic proton signals and four oxygenated carbons (C-2, C-7, C-9, and C-4 0 ). Similar to 1, compound 2 also possessed four oxygenated carbons but showed six aromatic protons and a methoxy carbon at C-4 0 .…”
Section: Chemical Structure Identificationmentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of an olefinic group [δ H 8.27-8.33 (H-2)/δ C 152.7-153.1 (C-2), and δ C 123.1-124.7 (C-3)] and a ketone carbon δ C 174.5-174.6 (C-4) in the 1 H-and 13 C-NMR spectra indicated 1, 2, and 5 to be isoflavones. 16,20 Comprehensive analysis of the 1 H-and 13 C-NMR spectra of 1 showed that 1 possessed 7 aromatic proton signals and four oxygenated carbons (C-2, C-7, C-9, and C-4 0 ). Similar to 1, compound 2 also possessed four oxygenated carbons but showed six aromatic protons and a methoxy carbon at C-4 0 .…”
Section: Chemical Structure Identificationmentioning
confidence: 99%
“…10,11 D. oliveri has been used to treat chronic ulcers, 10 and has been reported to possess various pharmacological activities, such as anti-tumor promoting, 12 cytotoxic and anti-fungal, 13 larvicidal, 14,15 and cell proliferation activity. 16 Previous studies on chemical constituents of D. oliveri showed the presence of isoflavones, isoflavanones, isoflavans, neoflavones, coumestones, coumarins, flavanones, chalcones, and pterocarpans. [12][13][14][15][16][17] Despite the number of studies, there has been no investigation of chemical constituents and inhibitory activity of NO production of Vietnamese D. oliveri.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In 2003, 7,2′-dihydroxy-4′,5′-dimethoxyisoflavanone ( 1 ) was first isolated from the heartwood of Dalbergia louvelii R. Viguier (Fabaceae), which was used as a folk medicine to treat bilharzia and malaria in Madagascar [ 13 ]. More recently, 1 and its structurally related phytochemicals possessing diverse substitution patterns and oxidation states were isolated from the bark of Dalbergia oliveri Prain, a traditional Thai medicine used for the treatment of chronic ulcers in Southeast Asia ( Figure 1 ) [ 14 ]. Isoflavanone 1 exhibits potent hair growth effects on immortalized dermal papilla cells (iDPCs).…”
Section: Introductionmentioning
confidence: 99%
“…Isoflavanone 1 exhibits potent hair growth effects on immortalized dermal papilla cells (iDPCs). In a cell proliferation assay, 1 induced significant cell proliferative activity (54.1% at 10 μM, EC 50 = 8.83 μM), which was more potent than that of Minoxidil (20.6% at 10 μM), a widely used medication for the prevention and treatment of hair loss [ 14 ]. Moreover, isoflavanone 1 induced the anagen phase of the hair cycle in a mouse model via subcutaneous (SC) injection [ 15 ].…”
Section: Introductionmentioning
confidence: 99%